Relationship between Cognitive Ability and Storytelling in Posyandu Lansia Sejahtera Mojosongo Surakarta - Nurul Dwi Rahmawati; Nadya Susanti (Sriwijaya Journal of Medicine, 2024)
Storytelling is a form of spoken language used to convey information or experiences experienced by the communicator to others. Storytelling activities call on cognitive functions such as the ability to think, absorb, capture, and concentrate. Declining cognitive functions certainly have a major impact on older people's ability to think, remember, learn, and use language. This study aims to determine whether there is a relationship between cognitive ability and the ability to tell stories in the elderly. The research design used was cross-sectional. The respondents in this study were 38 people aged 60, and the collection technique used was purposive sampling. The data analysis used was the contingency coefficient test. The results of this study showed a significant value of 0.003 (p<0.05), meaning that there is a relationship between cognitive ability and storytelling ability in the elderly.